Monographs on the move?: a view on 'decoupling' and other prospects. (26th September 2018) - Lockett, Andrew
In the context of the recent debate about the movement towards a monographs mandate for the UK, this opinion piece considers the logic of 'decoupling' that underlies it. It also looks at the real opportunities to improve on the current extraordinarily durable high-price system for publishing long-form research. Thinking around decoupled monograph publishing has positioned academic authors as the individual consumers of diverse publishing services (a wide array of which are fast emerging) in the face of significant scholarly caution. Furthermore, a danger of renewed market dominance by price-makers in an open access environment remains, with the risk of inequitable outcomes that may mirror problems that have arisen in journals. Opportunities may also arise for new local initiatives, especially collective and community-based publishing, with academic libraries likely to be in the middle of a fast-changing and contested environment for publishing monographs.